The Habaib in the Struggle for Indonesian Religious Authority Analysis of Bourdieu's Socio-Cultural Theory: Habaib Dalam Perebutan Otoritas Keagamaan Indonesia Analisis Teori Sosial Kultural Bourdieu - Shorfana, Muhammad Rizky; Subekti, Fiqi Restu; Aswar, Aswar; Zalsabila, Ayyesa Afrilia (Institut Agama Kristen Negeri Toraja, 2025)
Abstract: This study aims to explain how the religious authority of the habaib in Indonesia is reproduced through social and symbolic mechanisms. The focus of the study is directed at the question of how Pierre Bourdieu's concepts of habitus, capital, arena, and doxa can be used to understand the reproduction of the religious authority of the habaib in Indonesian Muslim society. This study analyzes the symbolic strategies and social practices implemented by the habaib group in maintaining and expanding their claims to religious authority. The approach used is qualitative with library research methods, with Pierre Bourdieu's works as primary sources and scientific literature related to the habaib and religious authority as secondary sources. The results show that religious practices such as haul, pilgrimage, shalawat assembly, taklim assembly, and the use of genealogical symbols form a religious habitus that functions to convert symbolic, cultural, and social capital into legitimacy of authority. In the competitive arena of religious authority, this process is reinforced through the production of doxa, so that the authority of the habaib is accepted as a religious truth that appears natural and sustainable in the collective consciousness of the community. Abstrak: Penelitian ini bertujuan menjelaskan bagaimana otoritas keagamaan habaib di Indonesia direproduksi melalui mekanisme sosial dan simbolik. Fokus kajian diarahkan pada pertanyaan bagaimana konsep habitus, modal, arena, dan doxa Pierre Bourdieu dapat digunakan untuk memahami reproduksi otoritas keagamaan habaib di tengah masyarakat Muslim Indonesia. Penelitian ini menganalisis strategi simbolik dan praksis sosial yang dijalankan kelompok habaib dalam mempertahankan serta memperluas klaim otoritas keagamaannya. Pendekatan yang digunakan adalah kualitatif dengan metode studi pustaka (library research), dengan karya-karya Pierre Bourdieu sebagai sumber primer serta literatur ilmiah terkait habaib dan otoritas keagamaan sebagai sumber sekunder. Hasil penelitian menunjukkan bahwa praktik keagamaan seperti haul, ziarah, majelis shalawat, majelis taklim, dan penggunaan simbol genealogis membentuk habitus keagamaan yang berfungsi mengonversi modal simbolik, budaya, dan sosial menjadi legitimasi otoritas. Dalam arena otoritas keagamaan yang kompetitif, proses tersebut diperkuat melalui produksi doxa, sehingga otoritas habaib diterima sebagai kebenaran religius yang tampak alamiah dan berkelanjutan dalam kesadaran kolektif umat.